The practical power flow analysis program based on matlab GUI developed for educational purposes for students in smart grids: Oyamatlab - Çınar, Mehmet; Kaygusuz, Asım (International journal of electrical engineering & education, 2024)
With the rapid development of today's technology, it has become possible to improve the electricity grid by using computer and network technologies in electricity networks. Thus, electricity grids will be able to provide sustainable, safe, and uninterrupted energy to consumers by allowing a two-way flow of information and electricity. Networks that can do this are called smart grids. Although conventional power lines have unidirectional power flow, a smart grid; enables the bidirectional flow of information and electricity by placing various hardware and software on the network. The main purpose of this study that tackles the smart grid is to introduce an educational program that can perform optimum load flow analysis based on Matlab GUI that can be used by undergraduate, graduate, and PhD students. Especially, students will be able to use the program easily in subjects related to loading flow analysis in electrical networks. Students using the program will have the opportunity to see different algorithm results in IEEE busbar systems and compare them with each other. The developed program realizes the optimum load distribution in bus systems accepted by IEEE in the smart grid using various metaheuristic algorithms and uses objective functions such as power losses, fuel cost, and voltage adjustment while performing optimum load distribution analysis. As a result of the program called Oyamatlab, optimum values in the selected busbar system are obtained. This is the program with a simple user interface for students to use without difficulty; it can perform optimum load distribution analysis by selecting different purpose functions.